Vaccines alone will not prevent COVID-19 outbreaks among migrant workers—the example of meat processing plants. (June 2022) - Fabreau, Gabriel E.; Holdbrook, Linda; Peters, Cheryl E.; Ronksley, Paul E.; Attaran, Amir; McBrien, Kerry; Pottie, Kevin
Abstract: Background: Migrant populations in high-income countries have faced myriad health and social inequities during the COVID-19 pandemic. Migrants often work in frontline essential services that expose them to COVID-19. Migrant workers in meat processing plants have endured large COVID-19 outbreaks across multiple countries. Objectives: We examine current scientific evidence around COVID-19 transmission, outcomes, and prevention for migrant workers and highlight meat processing plants as an example. Sources: We performed a series of PubMed searches between January 1, 2020 and January 12, 2022. Content: Migrant workers in high-income countries often work in occupations at high risk for COVID-19 transmission, contract COVID-19 at higher rates, and experience worse outcomes than native-born counterparts. For example, meat processing plants represent almost ideal environments for rapid and large-scale SARS-CoV-2 viral transmission; often, large migrant workforces confined to small workspaces perform physically demanding work in noisy environments that require shouting to communicate, increasing workers' respiratory rates and the quantity of aerosolized droplets expelled and thus increasing viral transmission risk. Although enhanced vaccination outreach programs remain an important equity approach for migrant worker safety, they alone are insufficient. The emergence and rapid spread of multiple increasingly transmissible SARS-CoV-2 variants of concern with variable vaccine escape properties, including Omicron in November 2021, highlight the importance of improved infection prevention and control strategies to protect migrant workers. Across countries, strategies such as improving ventilation and mask quality in many high-risk occupational settings are already required by employment law. Universal mandatory vaccination program should also be considered. Implications: COVID-19 transmission prevention for migrant workers requires an aggressive multicomponent plan that includes (a) improved on-site ventilation and infection prevention and control strategies; (b) improved social supports such as paid sick leave; (c) mobile vaccination clinics and community engagement to overcome vaccine hesitancy and barriers; and (d) consideration of universal mandatory vaccination programs.